Aislamiento social y deterioro cognitivo en adultos mayores de los Centros Gerontológicos de Babahoyo y Montalvo - Herrera Changoluisa, Tania Lizbeth (2025)
This study examines the relationship between social isolation and cognitive decline among elderly residents of geriatric centers in Babahoyo and Montalvo, Los Ríos province, Ecuador. It is based on the premise that social isolation, defined as a lack of meaningful interactions, is a risk factor for cognitive impairment. Using a descriptive and correlational approach, the living conditions and social dynamics of a sample of 100 older adults were analyzed. The findings underscore the importance of implementing intervention strategies to foster social interaction and mitigate the negative effects of isolation on this population. This research aims to contribute both to academia and to improving policies and practices in geriatric centers, promoting healthy and active aging.